2019
DOI: 10.3389/fchem.2019.00183
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Aerosol Assisted Pulsed Plasma Polymerization: An Environmentally Friendly Technique for Tunable Catechol-Bearing Thin Films

Abstract: In this work, an atmospheric aerosol assisted pulsed plasma process is reported as an environmentally friendly technique for the preparation of tunable catechol-bearing thin films under solvent and catalyst free conditions. The approach relies on the direct injection of dopamine acrylamide dissolved in 2-hydroxyethylmethacrylate as comonomer into the plasma zone. By adjusting the pulsing of the electrical discharge, the reactive plasma process can be alternatively switch ON (t ON ) and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Materials in a gaseous state at room temperature are themselves applied as precursors, whereas materials that exist as liquids are mainly introduced to a plasma region as an aerosol via atomizing or bubbling with gas. GATP methods are commonly used for the deposition of polymer films [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], as this method allows in-line processing by moving either the APP devices or the substrates [ 39 ].…”
Section: Synthesis Methods Using Gas/aerosol-type Precursors (Gatp)mentioning
confidence: 99%
“…Materials in a gaseous state at room temperature are themselves applied as precursors, whereas materials that exist as liquids are mainly introduced to a plasma region as an aerosol via atomizing or bubbling with gas. GATP methods are commonly used for the deposition of polymer films [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], as this method allows in-line processing by moving either the APP devices or the substrates [ 39 ].…”
Section: Synthesis Methods Using Gas/aerosol-type Precursors (Gatp)mentioning
confidence: 99%
“…J. Profili et al compared coatings deposited from atomized HMDSO with and without TiO 2 and they found, as expected, a rough surface (R rms in the range 32-60 nm) when NPs where present in the feed, but the morphology was also influenced by source voltage waveforms [60]. V. Jalaber et al demonstrated that the duty cycle of a pulsed source can be controlled to tune the morphology of catechol-containing films [80].…”
Section: Coupling Aerosols To Plasma Depositionmentioning
confidence: 75%
“…The properties of the resultant polypyrrole self-supporting thin films (e.g., their thickness, conductivity, and roughness) were determined by operating parameters such as discharge length and intensity, flow of processing argon gas, and the presence of nitrogen gas. The mechanism of polymer formation under these conditions is significantly different from that on the solid surface from volatile precursor, and to that during atmospheric aerosol assisted pulsed plasma polymerization [ 86 ]. Briefly, the collisions between plasma-generated electrons and N 2 molecules in air results in the generation of nitrogen-containing species including free radicals, some of which reach the interfacial layer between the gas and liquid phases, diffusing across this layer into the microemulsion.…”
Section: Plasma For Hydrophilicity and Hydrophobicity Control Of Polymersmentioning
confidence: 99%